Writing for mobile media: The influences of text, digital design and psychological characteristics on the cognitive load of the mobile user - Speechly, Amanda Karen (Centre for Film and Media Studies, 2020)
Text elements on the mobile smartphone interface make a significant contribution to the user’s interaction experience. In combination with other visual design features, these words curate the path of the mobile user on a journey through the information to satisfy a specific task. This study analyses the elements that influence the interpretation process and optimum presentation of information on mobile media. I argue that effective digital writing contributes to reducing the cognitive load experienced by the mobile user. The central discussion focuses on the writing of text for this medium, which I suggest forges an entirely unique narrative. The optimum writing approach is based on the multi-dimensional characteristics of hypertext, which allow the writer to facilitate the journey without the user losing control of the interpretation process. This study examines the relationship between the writer, the reader and the text, with a unique perspective on the mobile media writer, who is tasked with achieving balance between the functionality and humanity of digital interaction. To explore influences on the development of the relevant writing techniques, I present insights into the distinctive characteristics of the mobile smartphone device, with specific focus on the screen and keyboard. I also discuss the unique characteristics of the mobile user and show how the visual design of the interface is integral to the writing of text for this medium. Furthermore, this study explores the role, skills, and processes of the current and future digital writer, within the backdrop of incessant technological advancement and revolutionary changes in human-computer behaviour.